Edukasi dan Pelatihan Pembuatan Dish Soap dari Limbah Kulit Nanas untuk Meningkatkan Kewirausahaan UMKM di Desa Tangkit Baru - Rahmi, Silvi Leila; Wulansari, Dian; Mursyid; Fiardilla, Fauziah; Prihantoro, Rudi (WIDA Publishing, 2024)
This Community Service Program (PPM) aims to enhance the knowledge and skills of the residents of Tangkit Baru Village, particularly MSME entrepreneurs, in utilizing pineapple peel waste as an innovative material for dish soap production. The program also focuses on developing entrepreneurial spirit by transforming this waste into economically valuable products. The main goal of this activity is to address the issue of waste from pineapple processing and create new, sustainable products, thereby improving the local economy. The PPM activities were conducted in three stages: (1) Providing material on utilizing pineapple waste into economically viable products, (2) Demonstrating the process of making dish soap from pineapple peel, and (3) Discussing with participants the soap-making process. The results showed an increase in the community's understanding of the potential use of pineapple peel waste, as well as a high interest in this product innovation as a new business opportunity.